Dose-response relation between dietary sodium and blood pressure: a meta-regression analysis of 133 randomized controlled trials. Issue 5 (26th April 2019) - Graudal, Niels; Hubeck-Graudal, Thorbjørn; Jürgens, Gesche; Taylor, Rod S
ABSTRACT: Background: The projected reduced mortality effect of reduced sodium intake in model-based studies conflicts with the observed increased mortality associated with low sodium intake in population studies. This may reflect an overestimation of the dose-response relation between sodium reduction (SR) and blood pressure (BP) used in mortality modeling studies. Objectives: The present meta-regression analysis sought to estimate the dose-response relations between SR and BP in study groups with mean BP above or below the 75th percentile of the general population. Methods: Based on a literature search from 1 January 1946 to 11 April 2018, we identified 133 randomized controlled trials allocating healthy or hypertensive individuals to SR or usual sodium intake. Multivariable regression analyses of the mean SR versus the mean blood pressure effect adjusted for effect modifiers were performed. Results: In study groups with mean BP above the 75th percentile [131/78 mm Hg systolic BP (SBP)/diastolic BP (DBP)], there was strong evidence of a linear dose-response relation between SR and BP. For SBP, the dose-response relation was −7.7 mm Hg/100 mmol SR (95% CI: −10.4, −5.0), and for DBP it was −3.0 mm Hg/100 mmol SR (95% CI: −4.6, −1.4). In study groups with mean BP ≤ 131/78 mm Hg, the relation between SR and BP was weak. For SBP it was −1.46 mm Hg/100 mmol SR (95% CI: −2.7, −0.20) and for DBP it was: −0.07 mm Hg/100 mmol SR (95% CI: −1.5, 1.4). Conclusions: Only study groups with a BP in the highest 25th percentile of the population showed a clinically significant drop in BP with SR. The policy of lowering dietary sodium intake in the general population may need to be reframed to target patients with hypertension. This study was registered at PROSPERO 2015 as CRD42015017773.